THE EFFECT OF ACCOUNTING INFORMATION SYSTEMS, MANAGEMENT SUPPORT, AND EMPLOYEE TRAINING ON TRANSACTION PROCESS EFFICIENCY - Anak Agung Ngurah Agung Hari Wirama; Ni Luh Sari Widhiyani (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
Efficiency in the context of Accounting Information Systems (AIS) is the ability of a system to process financial data (input) into report information (output) at minimal cost, in the fastest time, and with zero error rate. Currently, 24 regional development banks in Indonesia have digital banking services with transaction volume growth reaching 48.2% year-on-year. This study found that the increase in transaction volume related to teller activities could pose risks. The purpose of this study was to obtain empirical evidence of the influence of accounting information systems, management support, and employee training on transaction process efficiency. This study used a quantitative associative approach. The sampling method used in this study was non-probability sampling with census sampling technique. The research location was at the Bali Regional Development Bank (BPD Bali) Main Branch in Denpasar with 54 employee samples who used AIS in their duties. The test results showed that accounting information systems, management support, and employee training had a positive effect on transaction process efficiency. Theoretically, this study reinforces the Technology Acceptance Model (TAM) and Theory of Planned Behavior (TPB) by proving that accounting information systems, management support, and employee training have a positive effect on transaction process efficiency. Practically, these results recommend that the management of BPD Main Branch Denpasar implement an integrated approach through the optimization of OLIBS features, the allocation of real resources, and continuous training to maximize transaction speed and accuracy.